The Dilemma of the Use of Tetun Language in the Writing of Scientific Works in Timor Leste : Phenomenological Analysis at Universidade Da Paz - Martinus Nahak; Lena Ellita (CV. Ulil Albab Corp, 2022)
The purpose of this study is to describe the phenomena that occur in Timor Leste, especially the use of the Tetun language in writing scientific papers at the Universidade da Paz (UNPAZ). Based on the constitution of the Democratic Republic of Timor Leste (KRDTL) article 13 paragraph 1: Tetun and Portuguese are the official languages of RDTL. Phenomenology as the basis in this study with the basic assumptions of Armada (2018: 115) one of the most complex cases in the discipline of hermeneutics is related to language. Phenomenological analysis method (Fleet, 2018:335) which was pioneered by Edmund Husserl. The object is Tetun and the subjects are students and lecturers for writing scientific papers. The results of the study indicate that the dilemmas that arise from the use of Tetun in writing scientific papers include erro otografico ( orthographic errors ), and erro grammatica (Grammatical Errors) from the translation of theories or narratives and interpretations of scientific texts in Indonesian and Portuguese into Tetun, because most of the references in writing are in Indonesian. This can significantly affect an individual